Big data in spare parts supply chains: The potential of using product-in-use data in aftermarket demand planning. Issue 5 (4th June 2018) - Andersson, Joakim; Jonsson, Patrik
Abstract : Purpose: The purpose of this paper is to explore and propose how product-in-use data can be used in, and improve the performance of, the demand planning process for automotive aftermarket services. Design/methodology/approach: A literature review and a single case study investigate the underlying reasons for the demand for spare parts by conducting in-depth interviews, observing actual demand-generating activities, and studying the demand planning process. Findings: This study identifies the relevant product-in-use data and divides them into five main categories. The authors have analysed how product-in-use data are best utilised in planning spare parts with different attributes, e.g. different life cycle phases and demand frequencies. Furthermore, the authors identify eight potentially relevant areas of application of product-in-use data in the demand planning process, and elaborate on their performance effects. Research limitations/implications: This study details the understanding of what impact context has on the potential performance effects of using product-in-use data in aftermarket demand planning. Propositions generate several strands for future research. Practical implications: This study shows the potential impact of using product-in-use data, using eight different types of interventions for spare parts, in the aftermarket demand planning. Originality/value: The literature focusses on single applications of product-in-use data, but would benefit from considering the context of application. This study presents interventions and explores how these enable improved demand planning by analysing usage and effects.